Penerapan Eko-Interior pada Restoran Merah Putih di Bali - Faustine Farellya (Intra, 2017)
One of interior designer’s role in addressing environmental issues is applying eco-interior approach to the design concept. Application of eco-interior is necessary to instill environmentally responsible attitude. In addition, the application of eco-interior can help create a healthy, environmentally friendly space, and increase comfort and productivity. The aspects of eco-interiors include energy conservation, water conservation, indoor air quality, and material selections will serve as the analysis’ benchmark in this research. Restoran Merah Putih was chosen as the object of research because it has applied the principle of environmentally friendly to the building, both in terms of exterior and interior. This research aims to determine the application of the eco-interior aspects of Restoran Merah Putih building in Bali. The research method used is qualitative approach with descriptive analysis method. The result of this research is Restoran Merah Putih has applied the eco-interior aspect maximally to the effort of energy conservation and water conservation. The use of natural lighting has been maximized throughout the day in every area of the restaurant, and uses energy-efficient artificial lighting at night. In aspect of water conservation, the restaurant has implemented rainwater storage and waste-water treatment. While on the aspect of indoor air quality and material selections still not optimally applied in restaurant areas, such as lack of ventilation as well as materials and finishing on the interior elements (floor, wall, ceiling), furniture, nor decorative elements that are not entirirely environmentally friendly.